Anti-Breast Cancer and Pharmacokinetic Prediction of Isorhamnetin, Glucocapparine Capparisine A And B From Capparis Spinosa - Amaliyah, Alfiah; Hasan, Mohammed A.H.M (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
The discovery of new natural anticancer agents is considered a remarkable solution to prevent drug resistance and metastasis in breast cancer patients. The Capparis spinosa plant is widely known for its antioxidant and other therapeutic effects. This study aims to evaluate anti-breast cancer activity targeting Akt1 and HIF1A proteins of several phytochemicals in Capparis spinosa through in silico methods and their pharmacokinetic prediction. This research is an in-silico study involving Bioinformatics (PASS Analysis with STITCH & STRING), Molecular Docking, and pkCSM Analysis. According to bioinformatics methods, AKT1 and HIF1A were obtained as potential protein targets. In molecular docking to AKT1 protein, the docking score obtained for Isorhamnetin, Glucocapparine, Capparisine A, Capparisine B, and Ipatasertib as control were -6.2 kcal/mol, -5.3 kcal/mol, -4.9 kcal/mol, -4.9 kcal/mol, and -6.2 kcal/mol respectively. Meanwhile, the docking score for HIF1A protein for Isorhamnetin, Glucocapparine, Capparisine A, Capparisine B, and 2-methoxy estradiol as control was -5.2 kcal/mol, -4.7 kcal/mol, -4.4 kcal/mol, -4.3 kcal/mol, and -4.7 kcal/mol. The scores for each compound were like the controls in both proteins, indicating that the analyzed phytochemicals of Capparis spinosa have potential anti-breast cancer properties. Pharmacokinetic prediction for absorption, distribution, metabolism, excretion, and toxicity (ADMET) is also provided to help further studies and development for the compounds as anticancer drugs. This study provided data from in silico methods regarding anti-breast cancer supported with pharmacokinetic activities for Isorhamnetin, Glucocapparine Capparisine A, and Capparisine B, which will be helpful as a reference for other advanced research in the future.